A simple method to disperse eggs from lepidopteran scalelike egg masses and to observe embryogenesis. Issue 1 (11th January 2022) - Arai, Hiroshi; Ishitsubo, Yuna; Nakai, Madoka; Inoue, Maki N.
Abstract: Various insect species lay tiny, thin‐ and soft‐shelled eggs in a connected "egg mass". Especially in several lepidopteran species, the structure of such clustered eggs is covered with complicated scale‐like secretion, which has so far prevented analysis of individual embryos. However, few studies on methods to disperse egg clusters of such insects and to compare different methods have been carried out. To overcome these problems, we developed methods to separate egg masses into individual eggs, using two Tortricidae pests, Homona magnanima Diakonoff and Adoxophyes honmai Yasuda (Lepidoptera: Tortricidae). The eggs were successfully separated from each other using potassium hydroxide and sodium hypochlorite. Although the separated eggs no longer continued their embryogenesis, fixation with heptane–paraformaldehyde, permeabilization with heptane–methanol, and staining with several dyes enabled easy observation of embryogenesis. This protocol is expected to be applicable to other insect taxa and will facilitate further morphological and genetic studies in insects that lay egg masses. Abstract : Various insect species lay eggs in a connected "egg mass". Especially in several lepidopteran species, the structure of such clustered eggs is covered with a complicated scale‐like secretion, which has so far prevented the analysis of individual embryos. To overcome these problems, we developed methods to separate egg masses into individual eggs, using two Tortricidae pests, Homona magnanima Diakonoff and Adoxophyes honmai Yasuda (Lepidoptera: Tortricidae).